2018
DOI: 10.1111/ejn.13861
|View full text |Cite
|
Sign up to set email alerts
|

Reduced low‐frequency power and phase locking reflect restoration in the auditory continuity illusion

Abstract: Interruptions in auditory input can be perceptually restored if they coincide with a masking sound, resulting in a continuity illusion. Previous studies have shown that this continuity illusion is associated with reduced low-frequency neural oscillations in the auditory cortex. However, the precise contribution of oscillatory amplitude changes and phase alignment to auditory restoration remains unclear. Using electroencephalography, we investigated induced power changes and phase locking in response to 3 Hz am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Finally, the 3-4 Hz power increase was dampened when participants perceived a continuity illusion versus when they perceived an interruption. These findings were replicated, to a large extent, in a recent study by Kaiser et al (2018), who investigated induced power changes and phase locking in response to 3 Hz amplitude-modulated tones during the interval of an interrupting noise. Again, the authors observed an attenuation of 3 Hz power during continuity illusions in comparison to both continuous tones and veridically perceived interrupted tones.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…Finally, the 3-4 Hz power increase was dampened when participants perceived a continuity illusion versus when they perceived an interruption. These findings were replicated, to a large extent, in a recent study by Kaiser et al (2018), who investigated induced power changes and phase locking in response to 3 Hz amplitude-modulated tones during the interval of an interrupting noise. Again, the authors observed an attenuation of 3 Hz power during continuity illusions in comparison to both continuous tones and veridically perceived interrupted tones.…”
Section: Introductionsupporting
confidence: 57%
“…Given previous findings of attenuated low-frequency oscillations during auditory processing in ScZ (Doege et al, 2009;Brockhaus-Dumke et al, 2007), we expected perceptually relevant alterations in 3 Hz power during the ACI paradigm in patients. Behavioral and EEG data for the control group have been previously described by Kaiser et al (2018). The present study constitutes an important extension of this study with a focus on the examination of differences and commonalities in auditory restoration during the ACI paradigm between patients with ScZ and healthy controls.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The study by Kaiser et al . () suggests a multi‐faceted role for low‐frequency power in auditory perception: a desynchronization of theta over central electrodes could be involved in processes related to restoration of an interrupted sound, whereas its increase could be reflective of detecting auditory boundaries. On the other hand, the study by Moris Fernandez et al .…”
Section: General Consensus and Controversiesmentioning
confidence: 99%
“…The most compelling finding of the current study is the significant positive relationship between ZT intensity rating and single‐trial theta power showing that ZT illusions may be related to changes in higher‐order processing systems such as sensory gating and auditory memory recall. A link between changing low‐frequency oscillations and perception of auditory illusions has been shown in a recent study by Kaiser and colleagues (Kaiser, Senkowski, Roa Romero, Riecke, & Keil, ). In this article, they show that reduced theta power goes together with the perceptual restoration of a tone when a temporal gap is masked by adding noise.…”
Section: Discussionmentioning
confidence: 76%